2018
DOI: 10.1016/j.crme.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of heat transfer and sintering behavior during direct metal laser sintering of AlSi10Mg alloy powder

Abstract: Direct Metal Laser Sintering (DMLS) is one of the leading additive manufacturing processes, which produces complex metallic parts directly from the powder. One of the major problems of this rapid manufacturing process is an inhomogeneous temperature distribution, which leads to residual stress in the build part. Thus, temperature analyses must be performed, to better understand the temperature distribution and sintering behavior of the powder bed with a different laser recipe. In this study, a comprehensive th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The powder bed is assumed to be a continuous medium because of the small size (approximately 20 mm) of the metal powder, and thus, the effect of the porosity of the metal powder on thermal properties is assumed to be negligible because of its particle size. Other studies have used this approximation (Nazami et al, 2021;Panda and Sahoo, 2018;Samantaray et al, 2018) and this has been experimentally corroborated in Koh and Fortini (1973), which observed that for materials with high thermal conductivities, the ratio of powder to solid conductivity remains unaffected by temperature. The thermophysical properties of the metal powder used for this study, SS 316 L (Valencia and Quested, 2008), are listed in Table 1.…”
Section: Thermal Modelmentioning
confidence: 78%
“…The powder bed is assumed to be a continuous medium because of the small size (approximately 20 mm) of the metal powder, and thus, the effect of the porosity of the metal powder on thermal properties is assumed to be negligible because of its particle size. Other studies have used this approximation (Nazami et al, 2021;Panda and Sahoo, 2018;Samantaray et al, 2018) and this has been experimentally corroborated in Koh and Fortini (1973), which observed that for materials with high thermal conductivities, the ratio of powder to solid conductivity remains unaffected by temperature. The thermophysical properties of the metal powder used for this study, SS 316 L (Valencia and Quested, 2008), are listed in Table 1.…”
Section: Thermal Modelmentioning
confidence: 78%
“…Reason for 200 mm/s and 30 lm shows highest hardness is due to two different conditions one is that is get reinforced by Graphene (2 wt%) and other is scanning speed of printing [8,[15][16][17]. DMLS process at higher scanning speed, the time for recrystallization of the grains is observed to be less and thus the solidification occurred at very quickly which leads to creation of very small grain size [16][17][18]. From Fig.…”
Section: Hardness Validationmentioning
confidence: 91%
“…From the graph of both Rockwell as well as Vickers hardness graph sample of 200 mm/s and 30 lm shows higher hardness than the two other while sample 200 mm/s and 30 lm comes in between the other two. Reason for 200 mm/s and 30 lm shows highest hardness is due to two different conditions one is that is get reinforced by Graphene (2 wt%) and other is scanning speed of printing [8,[15][16][17]. DMLS process at higher scanning speed, the time for recrystallization of the grains is observed to be less and thus the solidification occurred at very quickly which leads to creation of very small grain size [16][17][18].…”
Section: Hardness Validationmentioning
confidence: 98%
“…Post-processing is required for secondary purposes because using low-power lasers to bind powder particles only melts the surface of the powder particles. AM process parameters such as laser power [108], scan speed [108], scan length [109], powder function [110], geometry [111], and distribution [112] are the 'inputs' that primarily determine the rate of energy delivered to the surface of the powder and how that energy interacts with the material. Process effects significantly influence final product qualities.…”
Section: Process-property (P-p) Relationshipmentioning
confidence: 99%